Association of the transcription profile of bovine oocytes and embryos with developmental potential - Kanka, J; Nemcova, L; Toralova, T; Vodickova-Kepkova, K; Vodicka, P; Jeseta, M; Machatkova, M (Animal reproduction science, 2012)
Although improvements in culture system have enhanced in vitro embryo production, success rates are still not adequate. The reasons for developmental arrest of a part of in vitro produced embryos are unknown, but are connected in part with low cytoplasmic competence of oocytes. The immaturity of cytoplasm can negatively influence fertilization efficiency and subsequent progression through embryonic genome activation (EGA), which are necessary steps in further pre-implantation development. A large number of studies have compared mRNA abundance among oocytes with different developmental competence with the aim to find markers of the normal embryo development. The amount of mitochondrial DNA (mtDNA) and mRNA for mitochondrial transcriptional factors directing oxidative phosphorylation belongs to such promising markers. Nevertheless, recently published studies revealed that the mammalian embryo is able to compensate for a reduced level of mtDNA in oocyte during subsequent pre-implantation development. The search for other molecular markers is in progress. Characterization of oocyte and embryonic mRNA expression patterns during the pre-implantation period, and their relationship to the successful in vitro and in vivo development will be essential for defining the optimized culture conditions or the nuclear transfer protocols. Microarrays technology enables us to reveal the differentially expressed genes during EGA, and to compare the expression profile of in vivo and in vitro produced embryos. Recent evidence indicates that the depletion of the pool of stored maternal mRNAs is critical for subsequent embryo development. All these experiments gradually offer a list of possible candidates for quality and developmental competence markers for mammalian oocytes and pre-implantation embryos.
Keywords: genetická transkripce; Transcription, Genetic; oocyty; Transcriptome; Female; Gene Expression Regulation, Developmental; RNA, Messenger; vývojová regulace genové exprese; transkriptom; Animals; Cattle; ženské pohlaví; Oocytes; messenger RNA; zvířata; skot